Index Card Match Learning Method to Improve Learning Concentration - Raihan, Paqih; Tabroni, Imam; Wang, Yuanyuan; Zou, Guijiao (Journal of Computer Science Advancements, 2023)
This study was motivated by the results of observations of researchers in class XI MA Daarul Ma'arif Pasawahan students in the PAI learning process in class. From the observation, it is known that there are still many students who do not pay attention to the teacher's explanation when delivering material in class. The concentration of students' learning is low, namely 62.5% of 29 people with a minimum completeness criteria of 75. Classical completeness is declared incomplete. This study aims to determine that the application of the index card match learning method can increase the concentration of PAI learning in class XI MA Daarul Ma'arif Pasawahan. This research was conducted in class XI MA Daarul Ma'arif Pasawahan. This research was conducted from February 2023 to May 2023. The subjects of this study were grade XI students with a total of 29 students consisting of 19 female students 10 male students. The form of this assessment is a class action assessment (PTK). The results showed that the application of the index card match method can increase the concentration of PAI learning in class XI students of MA Daarul Ma'arif Pasawahan in 2022/2023. The concentration of student learning before PTK was 66.7 with a category of less and classical completeness was 62.5% with an incomplete category. Learning concentration of cycle I meeting 1 was 75.8 with sufficient category and classical completeness was 87.5% with complete category. Learning concentration of cycle I meeting 2 was 79.2 with sufficient category and classical completeness was 91.7% with complete category. Cycle II learning concentration with meeting 3 was 82.1 with good category and classical completeness was 95.8% with complete category. Learning concentration of cycle II with meeting 4 was 87.9 with good category and classical completeness was 100% with complete category.